2014
DOI: 10.1080/15287394.2014.926801
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Hemorrhagic Stroke Hospitalization and Exposure to Fine Particulate Air Pollution in Taipei, Taiwan

Abstract: This study was undertaken to determine whether there was a correlation between fine particle (PM2.5) levels and hospital admissions for hemorrhagic stroke (HS) in Taipei, Taiwan. Hospital admissions for HS and ambient air pollution data for Taipei were obtained for the period 2006-2010. The relative risk of hospital admissions was estimated using a case-crossover approach, controlling for weather variables, day of the week, seasonality, and long-term time trends. For the single-pollutant model (without adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…PM 2.5 is associated with increased hemorrhagic stroke admissions on both warm (>23 C) and cold (< 23 C) days. [56] Further, PM 2.5 increases the relative risk of hospital admissions caused by ischemic stroke by 11% on warm days (>23 C) and by 4% on cold days (<23 C) in Taiwan. [57] Warm temperature (>13.5 C) was associated with increased hospital admissions for ischemic and hemorrhagic stroke during short-term exposure to PM 2.5 , PM2.5–10 and PM 10 individually.…”
Section: Air Pollution and Strokementioning
confidence: 99%
“…PM 2.5 is associated with increased hemorrhagic stroke admissions on both warm (>23 C) and cold (< 23 C) days. [56] Further, PM 2.5 increases the relative risk of hospital admissions caused by ischemic stroke by 11% on warm days (>23 C) and by 4% on cold days (<23 C) in Taiwan. [57] Warm temperature (>13.5 C) was associated with increased hospital admissions for ischemic and hemorrhagic stroke during short-term exposure to PM 2.5 , PM2.5–10 and PM 10 individually.…”
Section: Air Pollution and Strokementioning
confidence: 99%
“…The relationship between PM 2.5 exposure and stroke hospitalization was reported in several epidemiological investigations Chiu et al, 2014;Wang et al, 2014). Motor, cognitive, and behavioral changes were also noted in humans and animals after airborne PM exposure (Lucchini et al, 2007;Win-Shwe et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Epidemiological investigations demonstrated that exposure to PM 2.5 increased the risk of developing respiratory diseases and lung cancer (Cui et al, 2015;Pope et al, 2011;Tsai et al, 2014b), as well as enhanced mortality and hospitalization rates for cardiovascular diseases (Chang et al, 2013, Chiu et al, 2014Lipsett et al, 2011;Thurston et al, 2015). Yang et al (2014) and Chiu et al (2014) showed that PM 2.5 exposure was associated with a higher frequency of stroke hospitalizations and mortality in humans. However, the mechanisms underlying PM 2.5 -mediated development of ischemic stroke (IS) are not fully understood.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Haemorrhagic stroke is less common than ischaemic stroke leading to lower statistical power and fewer studies considering it as a separate outcome. However, two recently published studies in Taiwan provided evidence of positive associations between hospital admission for haemorrhagic stroke and exposure to PM 2.5 (particularly on warm days), 4 and between emergency room visits for haemorrhagic stroke and the same day exposure to the PM 2.5 components nitrate and elemental carbon. 5 Further studies with sufficient information to distinguish between stroke subtypes (eg, ischaemic and haemorrhagic) are therefore required.…”
Section: Introductionmentioning
confidence: 99%